PROTOTYPE SISTEM CONTROL BERBASIS INTERNET OF THINGS PADA PENYINARAN KEBUN BUAH NAGA - Charis Charis Fathul Hadi (PTE FTK UIN Ar-Raniry, 2020)
In supplying the dragon fruit market, dragon fruit farmers use irradiation methods in the off-season to increase the productivity of dragon fruit harvests, with manual dragon irradiation methods seen as less effective in the process of irradiating the operation, the role of technology can be used in the irradiation control system of dragon fruit gardens. based on the internet of things in order to be effective in operating the irradiation of dragon fruit garden lights in a long distance and produce maximum out of season harvest. The study was conducted in 4 stages: needs survey, design, prototype, trial. In the trial using the ESP 8266 wifi module, the module has the disadvantage that it is easy to heat when searching for a wifi signal that is used in the process of transmitting light control system data which is assumed to be the irradiation of the dragon fruit garden, so that it can cause problems in the internet connection. But in the results of testing the IoT-based control system which is assumed to irradiate the dragon fruit kebuh in 4 well-controlled lights with 100% success. In this research it is recommended to use the ESP 8266 wifi mode with good internet facilities because ESP 8266 can work optimally by an internet connection. If the internet connection used is unstable, it will make the ESP 8266 module become hot so it can make the module burn